2023
DOI: 10.1177/17455057231172355
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of mothers toward HPV vaccination: A cross-sectional study in Kazakhstan

Abstract: Background: Although recommended for all member states of World Health Organization, there is no national human papillomavirus vaccination program in Kazakhstan. Furthermore, there are no studies in Kazakhstan that evaluate the mothers’ perception of human papillomavirus vaccines. Objectives: This study aims to assess the knowledge and attitudes toward human papillomavirus vaccination among mothers in Kazakhstan and the factors associated with their attitudes. Design: A cross-sectional study was performed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
8
3
Order By: Relevance
“…In conclusion, our study revealed the higher-than-expected prevalence of STIs among women attending OB/GYN clinics in the MENA region, emphasizing the significance of reinforcing STI surveillance to develop a better understanding of the burden of these infections nationwide and monitor infection trends over time [ 17 ]. Our findings also underscore the imperative for targeted prevention interventions, including HPV immunization [ 26 ], enhanced access to sexual health services, integration of STIs into routine screening protocols, and improved linkage to care [ 14 , 25 ]. Implementing these strategies is essential to reducing STI incidence and mitigating their adverse impact on women’s health, social well-being, and economic welfare.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In conclusion, our study revealed the higher-than-expected prevalence of STIs among women attending OB/GYN clinics in the MENA region, emphasizing the significance of reinforcing STI surveillance to develop a better understanding of the burden of these infections nationwide and monitor infection trends over time [ 17 ]. Our findings also underscore the imperative for targeted prevention interventions, including HPV immunization [ 26 ], enhanced access to sexual health services, integration of STIs into routine screening protocols, and improved linkage to care [ 14 , 25 ]. Implementing these strategies is essential to reducing STI incidence and mitigating their adverse impact on women’s health, social well-being, and economic welfare.…”
Section: Discussionmentioning
confidence: 72%
“…There is a pressing need to integrate HPV screening into routine assessments for women of reproductive age in Lebanon and other Middle East and North Africa region (MENA) countries or, at the very least, to enhance awareness about the significance of HPV screening among women [ 25 ], akin to the campaigns established for breast cancer awareness [ 14 , 25 , 26 ]. Several cultural, economic, and access to healthcare factors contribute to the rising, but not fully documented, prevalence of STIs [ 6 , 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding was higher than the study done in Kazakhstan, 47% of the mothers who had negative attitudes toward HPV vaccination. 7 This may be due to the fact that in Kazakhstan, parental consent is required for medical interventions for children under 18 years.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Although recommended for all member states of WHO, HPV vaccination has not been implemented in Kazakhstan yet. 7 In Ethiopia, the vaccine was launched in 2018; recently, the vaccine was given for 9–14-year-old females in two doses at 6-month intervals. 8 …”
Section: Introductionmentioning
confidence: 99%
“…8 In particular, attitudes of mothers toward HPV vaccination are greatly impacted by health education and focused awareness initiatives, crucial factors in ensuring their children receive the vaccine. 9 Mathematical models have been developed to understand complex network structures in fields such as epidemiology, social dynamics, signaling networks, and neuroscience. 10 In particular, disease transmission has been investigated.…”
mentioning
confidence: 99%